UK victim-survivor experiences of intimate partner spiritual abuse and religious coercive control and implications for practice - Mulvihill, Natasha (Criminology & criminal justice, 2023)
This study extends existing scholarship on coercive control within an intimate relationship by exploring how some perpetrators use spiritual abuse as part of their control repertoire and how others harness belief and doctrine to exercise a totalising ‘religious coercive control’ over their victims. The analysis in this article draws on two multi-faith datasets: secondary data analysis of 27 semi-structured interviews and primary data collected through an online anonymous survey eliciting 24 qualitative responses, supplemented by 4 follow-up interviews with victim-survivors. Thematic analysis demonstrates the experience and longer-term impact of coercive control on victim-survivors and the barriers to help-seeking, including complicity at familial, community and leadership levels. We articulate their recommendations for change within places of worship and the implications for criminal justice practitioners.